QUESTION WORDS IN MOLLO DIALECT OF UAB METO SPOKEN IN NUNBENA VILLAGE, SOUTH CENTRAL TIMOR REGENCY - Juanto Canceriady Nalle; Yanpitherzon Liunokas; Elisna Huan; Gracia M. N. Otta (Jurnal Pendidikan dan Sastra Inggris, 2022)
This study is entitled: Question Words In Mollo Dialect Of Uab Meto Spoken In Nunbena Village, South Central Timor Regency. The problems of this study is to find out the question words and their function in Mollo dialect of Uab Meto spoken in Nunbena Village, South Central Timor Regency. In order to get the data, the writers selected five native speakers of Mollo dialect of Uab Meto from Nunbena Village as informants. The instrument of this study is the writers themselves which assisted by using list of sentences in the form of questions. He provided list of questions in Indonesian, and the informants were asked to translate them into Mollo dialect of Uab Meto. Observation, interview, recording and note taking were the data collection techniques of this study. The writer analyzes the data by using three procedures, namely: identifying, classifying and describing. The result shows that: (1). there are nine question words that are used to express interrogatives in Mollo dialect of Uab Meto, namely: sa/sa’an (what), leka (when), sekau (who, whom,), onme (how), esme/makome/noime (where), le’me (which), nansa (why), fauk (how many and how much) and ai/ait (auxiliary)